An Unusual Presentation of Adenoid Cystic Carcinoma. (24th December 2015) - Gill, Kurren S.; Frattali, Mark A.
Abstract : Adenoid cystic carcinoma (ACC) is a relatively rare tumor of epithelial cell origin, most commonly arising from major salivary glands. It is uncommonly found outside the major or minor salivary glands and is especially rare when located in the nasal cavity. Diagnosis and treatment of ACC pose numerous challenges, partly due to its biological behavior of slow growth, high tendency of local recurrence, and perineural invasion. We present the case of a 67-year-old male with complaints of facial pain and swelling, with a CT scan showing a soft tissue mass extending from the right nasal cavity with osseous destruction. Biopsy revealed ACC with perineural invasion. ACC of the nasal cavity continues to pose diagnostic and therapeutic challenges to physicians. Because this rare pathology presents in a vague manner, early diagnosis requires a high index of suspicion for this disease and close follow-up care. Since ACC of the nasal cavity is seldom reported in the literature, it is our hope that reporting these rare instances as case reports will heighten physician awareness of this rare disease, allowing for early diagnosis and treatment.